Regional Business‐Cycle Synchronization, Sector Specialization and EU Accession1. (30th July 2015) - Bierbaumer‐Polly, Jürgen; Huber, Peter; Rozmahel, Petr
Abstract: We examine the effects of Eastern and Northern enlargement of the EU on regional business‐cycle synchronization and sector specialization. Difference‐in‐difference estimates show that cyclical synchronicity decreased and differences in sector structure increased in acceding region‐pairs after Eastern enlargement. For Northern enlargement, results are more ambiguous. Moreover, in both enlargement episodes, region‐pairs with highly synchronous business cycles before accession experienced weaker cyclical and structural convergence than region‐pairs with less synchronous cycles. Likewise, region‐pairs with more similar sector structures before accession experienced stronger divergence (or weaker convergence) of structural similarity and business‐cycle synchronicity after the enlargement. We argue that these results call for developing more differentiated hypotheses on EU enlargement's effects on business‐cycle synchronization and sector specialization.